The Various of Complete Feed Block for Dairy Cattle - Munasik, Munasik; Anwar, Syaiful; Prajitno, Caribu Hadi (ANIMAL PRODUCTION, 2014)
Abstract. The effect of three forms of complete feed blocks (CFB) for dairy cattle was evaluated. The form of various CFB were cube, cylinder and ball.  The CFB was prepared from napier grass specific tolerance acid soils and concentrate in 50:50 ratio.  The research used experimental method with randomized block design.   Sixteen dairy cattle were used in this experiment.  There were four treatments and four replications used in this experiment.  The treatments consisted of R0= control ration, R1= cube CFB, R2= cylinder CFB and R3= ball CFB.  The treatment feeds were fed twice a day, at 6.00 am and 15.00 pm.  The amount of morning ration 34 kg of fresh napier grass and 5 kg of concentrate for the control ration, and the same amount of ration was also given in the afternoon feeding, therefore, the daily total fresh forage was 68 kg and concentrate was 10 kg.  Before feeding the forage was chopped in 5 cm length.  The complete feed block for the dairy cows was 10 kg for the morning ration and 10 kg for the afternoon ration, therefore, the daily total complete feed block was 20 kg.  The drinking water was available adlibitum.  The preliminary period was conducted for 2 weeks and data collection were conducted for 5 day of the end of study. The variables measured were dry matter and organic matter intake, dry matter digestibility and milk production.  These results showed that the control ration significantly affected with  ration all CFB form on dry matter and organic matter intake but did not significantly affect the dry matter digestibility and milk production. Key words : dairy cttle, complete feed block Abstrak.Penelitian ini bertujuan mengevaluasi pengaruh tiga pakan komplit bentuk cetak yaitu bentuk kubus, silinder dan bola yang diberikan pada sapi perah.   Pakan komplit bentuk cetak dibuat dari hijauan rumput gajah yang spesifik toleran tanah masam yang telah digiling dan bahan konsentrat dengan perbandingan 50:50.  Rancangan percobaan yang digunakan adalah rancangan acak kelompok.  Enam belas ekor sapi perah dikelompokkan menjadi 4 dengan 4 ulangan.  Empat perlakuan yang dicobakan yaitu R0= ransum kontrol, R1= pakan komplit cetak bentuk kubus, R2= pakan komplit cetak bentuk silinder, dan R3= pakan komplit cetak bentuk bola. Pakan perlakuan diberikan dua kali sehari pagi pukul 06.00 dan sore 15.00.  Jumlah pakan  yang diberikan pada sapi perah kontrol pagi sebanyak 34 kg rumput gajah segar dan 5 kg konsentrat demikian juga pemberian yang sama pada sore hari sehingga jumlah hijauan segar yang diberikan kepada ternak 68 kg dan konsentrat 10 kg.  Rumput gajah yang diberikan sudah dipotong-potong terlebih dahulu dengan panjang 5 cm.  Jumlah pakan komplit cetak untuk sapi perah perlakuan yang diberikan pagi jumlahnya sama dengan pemberian sore masing-masing sebanyak 10 kg sehingga jumlah pakan komplit cetak yang diberikan 20 kg.  Air minum diberikan adlibitum.  Periode preliminary dilakukan selama 2 minggu dan koleksi data dilakukan selama 5 hari periode akhir percobaan.  Variabel yang diamati adalah konsumsi bahan kering dan bahan organik pakan, kecernaan bahan kering pakan dan produksi susu.  Hasil penelitian menunjukkan bahwa ransum kontrol beda nyata dengan semua bentuk pakan komplit cetak pada konsumsi bahan kering dan bahan organik, akan tetapi tidak berbeda nyata dengan  kecernaan bahan kering dan produksi susu. Kata kunci : sapi perah, pakan komplit bentuk cetak